Environmental and practice factors associated with children's device-measured physical activity and sedentary time in early childhood education and care centres: a systematic review - Anne Martin; Rachel Brophy; Joanne Clarke; Charlotte J. S. Hall; Russell Jago; Ruth Kipping; Tom Reid; Benjamin Rigby; Hilary Taylor; James White; Sharon A. Simpson (BMC, 2022)
Abstract Background Early childhood education and care (ECEC) settings offer a potentially cost-effective and sustainable solution for ensuring children have opportunities to meet physical activity (PA) and sedentary time (ST) guidelines. This paper systematically reviewed the association between childcare environment and practice and children's PA and ST. Methods Three electronic databases were searched, and citation tracking of eligible studies performed between June-July 2020 (updated March 2022). Studies were eligible when (i) participants attended ECEC settings, (ii) they reported the association between use of outdoor space, including factors of time, availability, play, size and equipment, and children's device-measured PA and ST, and (iii) where applicable, they compared the exposure to use of indoor space. Risk of bias was assessed using the Critical Appraisal Skills Program (CASP) tools. A synthesis was performed using effect direct plots and charts to visualise effect sizes. Results Of 1617 reports screened, 29 studies met the inclusion criteria. Studies provided data on outdoor versus indoor time (n = 9; 960 children), outdoor versus indoor play (n = 3; 1104 children), outdoor play space (n = 19; 9596 children), outdoor space use external to ECEC (n = 2; 1148 children), and portable (n = 7; 2408 children) and fixed (n = 7; 2451 children) outdoor equipment. Time spent outdoors versus indoors was associated with increased moderate-to-vigorous PA (MVPA), light PA (LPA) and total PA, while the association with ST was inconclusive. The mean (standard deviation) levels of outdoor MVPA (4.0 ± 3.2 to 18.6 ± 5.6 min/h) and LPA (9.9 ± 2.6 to 30.8 ± 11.8 min/h) were low, and ST high (30.0 ± 6.5 to 46.1 ± 4.3 min/h). MVPA levels doubled when children played outdoors versus indoors. Outdoor play space, and outdoor portable equipment, were associated with increased MVPA. A dose-response relationship for outdoor play area size was observed, demonstrating increased MVPA with areas ≥505m2 (5436 ft2), but no further increases when areas were > 900m2 (9688 ft2). No studies reported on injuries in outdoor settings. Conclusions ECEC policies and practices should promote not only outdoor time but also the availability of resources such as portable play equipment and sufficient size of outdoor play areas that enable children to be physically active for sustained periods while outdoors. Systematic review registration International prospective register of systematic reviews (PROSPERO) Registration Number: CRD42020189886.